THE IRON TRIANGLE AS THE TRIPLE CONSTRAINTS IN PROJECT MANAGEMENT - Hafnidar Abdul Rani (Jurnal Teknik Sipil, 2013)
AbstractProject Management can be used as a tool to maximize the success of a project. Empirically, there is strong evidence that the practice of project management knowledge can affect of the project success. Time, cost and quality, over the last 50 years have become inextricably linked with measuring the success of project. The iron triangle are the principle criteria for the project success. In fact, almost every plan relating to mention three of them and show the importance of criteria in project development. This is perhaps not surprising, since over the same period those criteria are usually included in the description of project management. Time and costÂ  are best guesses, typically calculated when less is known during the planning phases, and quality is an attitude that changes over the project life cycle. The iron triangle comprises three well recognized criteria against which project success is measured. The measure of project success is how far the triple constraints can be filled out.Keywords : Project management; iron triangle; triple constraints; project success.Abstrak :Manajemen proyek dapat digunakan sebagai alat untuk memaksimumkan kesuksesan proyek. Secara empiris, ada bukti kuat bahwa praktik pengetahuan manajemen proyek dapat mempengaruhi keberhasilan proyek. Waktu, biaya dan kualitas, selama 50 tahun terakhir telah menjadi terkait erat dengan mengukur keberhasilan proyek. The iron triangle adalah criteria asas untuk keberhasilan proyek. Malah hampir setiap rencana berkaitan menyebutkan ketiga-tiganya dan menunjukkan pentingnya kriteria itu dalam proyek konstruksi. Hal ini mungkin tidak mengherankan karena selama tempo yang sama kriteria selalu termasuk dalam deskripsi manajemen proyek. Waktu dan biaya merupakan terkaan terbaik yang biasanya dikira jika kurang dikenali selama fasa perencanaan dan kualitas merupakan suatu sikap perubahan selama kitaran hidup proyek. The Iron triangle terdiri dari tiga criteria yang dikenali dengan bai terhadap keberhasilan proyek yang diukur. Ukuran keberhasilan proyek adalah sejauh mana tiga kendala dapat diisi.Kata kunci : manajemen proyek; iron triangle; tiga kendala; keberhasilan proyek.